On the design principles of peptide–drug conjugates for targeted drug delivery to the malignant tumor site - Vrettos, Eirinaios I.; Mező, Gábor; Tzakos, Andreas G. (Beilstein Journal of Organic Chemistry, 2018)
Cancer is the second leading cause of death affecting nearly one in two people, and the appearance of new cases is projected to rise by >70% by 2030. To effectively combat the menace of cancer, a variety of strategies have been exploited. Among them, the development of peptide–drug conjugates (PDCs) is considered as an inextricable part of this armamentarium and is continuously explored as a viable approach to target malignant tumors. The general architecture of PDCs consists of three building blocks: the tumor-homing peptide, the cytotoxic agent and the biodegradable connecting linker. The aim of the current review is to provide a spherical perspective on the basic principles governing PDCs, as also the methodology to construct them. We aim to offer basic and integral knowledge on the rational design towards the construction of PDCs through analyzing each building block, as also to highlight the overall progress of this rapidly growing field. Therefore, we focus on several intriguing examples from the recent literature, including important PDCs that have progressed to phase III clinical trials. Last, we address possible difficulties that may emerge during the synthesis of PDCs, as also report ways to overcome them.
Keywords: bioconjugates; cancer; drug delivery; PDC; peptide; peptide–drug conjugate; side-products in PDCs

The global burden of disease - Organization, W. H. (World Health Organization, 2008)

(untitled) - Jemal, A.; Bray, F.; Center, M. M.; Ferlay, J.; Ward, E.; Forman, D. (Ca-Cancer J. Clin., 2011)

(untitled) - Yan, L.; Rosen, N.; Arteaga, C. (Chin. J. Cancer, 2011)

(untitled) - Mullard, A. (Nat. Rev. Drug Discovery, 2018)

(untitled) - Aggarwal, S. (Nat. Rev. Drug Discovery, 2010)

(untitled) - Szakács, G.; Paterson, J. K.; Ludwig, J. A.; Booth-Genthe, C.; Gottesman, M. M. (Nat. Rev. Drug Discovery, 2006)

(untitled) - Undevia, S. D.; Gomez-Abuin, G.; Ratain, M. J. (Nat. Rev. Cancer, 2005)

(untitled) - de Sousa Cavalcante, L.; Monteiro, G. (Eur. J. Pharmacol., 2014)

(untitled) - Bocci, G.; Kerbel, R. S. (Nat. Rev. Clin. Oncol., 2016)

(untitled) - Ferlay, J.; Steliarova-Foucher, E.; Lortet-Tieulent, J.; Rosso, S.; Coebergh, J. W. W.; Comber, H.; Forman, D.; Bray, F. (Eur. J. Cancer, 2013)

(untitled) - Kola, I.; Landis, J. (Nat. Rev. Drug Discovery, 2004)

(untitled) - Vander Heiden, M. G. (Nat. Rev. Drug Discovery, 2011)

(untitled) - Galluzzi, L.; Kepp, O.; Vander Heiden, M. G.; Kroemer, G. (Nat. Rev. Drug Discovery, 2013)

(untitled) - Bhat, M.; Robichaud, N.; Hulea, L.; Sonenberg, N.; Pelletier, J.; Topisirovic, I. (Nat. Rev. Drug Discovery, 2015)

(untitled) - Pfister, S. X.; Ashworth, A. (Nat. Rev. Drug Discovery, 2017)

(untitled) - Tai, W.; Mahato, R.; Cheng, K. (J. Controlled Release, 2010)

(untitled) - Zwicke, G. L.; Mansoori, G. A.; Jeffery, C. J. (Nano Rev., 2012)

(untitled) - Argyros, O.; Karampelas, T.; Asvos, X.; Varela, A.; Sayyad, N.; Papakyriakou, A.; Davos, C. H.; Tzakos, A. G.; Fokas, D.; Tamvakopoulos, C. (Cancer Res., 2016)

(untitled) - Karampelas, T.; Argyros, O.; Sayyad, N.; Spyridaki, K.; Pappas, C.; Morgan, K.; Kolios, G.; Millar, R. P.; Liapakis, G.; Tzakos, A. G.; Fokas, D.; Tamvakopoulos, C. (Bioconjugate Chem., 2014)

(untitled) - Kellici, T. F.; Chatziathanasiadou, M. V.; Lee, M.-S.; Sayyad, N.; Geromichalou, E. G.; Vrettos, E. I.; Tsiailanis, A. D.; Chi, S.-W.; Geromichalos, G. D.; Mavromoustakos, T.; Tzakos, A. G. (Org. Biomol. Chem., 2017)

(untitled) - DeBerardinis, R. J.; Chandel, N. S. (Sci. Adv., 2016)

(untitled) - Trachootham, D.; Alexandre, J.; Huang, P. (Nat. Rev. Drug Discovery, 2009)

(untitled) - Kato, Y.; Ozawa, S.; Miyamoto, C.; Maehata, Y.; Suzuki, A.; Maeda, T.; Baba, Y. (Cancer Cell Int., 2013)

(untitled) - Singh, R.; Lillard, J. W., Jr (Exp. Mol. Pathol., 2009)

(untitled) - Karakurt, S.; Kellici, T. F.; Mavromoustakos, T.; Tzakos, A. G.; Yilmaz, M. (Curr. Org. Chem., 2016)

(untitled) - Kellici, T. F.; Chatziathanasiadou, M. V.; Diamantis, D.; Chatzikonstantinou, A. V.; Andreadelis, I.; Christodoulou, E.; Valsami, G.; Mavromoustakos, T.; Tzakos, A. G. (Int. J. Pharm., 2016)

(untitled) - Tsume, Y.; Incecayir, T.; Song, X.; Hilfinger, J. M.; Amidon, G. L. (Eur. J. Pharm. Biopharm., 2014)

(untitled) - Apostolopoulos, V.; Pietersz, G. A.; Tsibanis, A.; Tsikkinis, A.; Drakaki, H.; Loveland, B. E.; Piddlesden, S. J.; Plebanski, M.; Pouniotis, D. S.; Alexis, M. N.; McKenzie, I. F.; Vassilaros, S. (Breast Cancer Res., 2006)

(untitled) - Tang, C. K.; Lodding, J.; Minigo, G.; Pouniotis, D. S.; Plebanski, M.; Scholzen, A.; McKenzie, I. F. C.; Pietersz, G. A.; Apostolopoulos, V. (Immunology, 2007)

(untitled) - Apostolopoulos, V.; McKenzie, I. F.; Pietersz, G. A. (Immunol. Cell Biol., 1996)

(untitled) - Tzakos, A. G.; Briasoulis, E.; Thalhammer, T.; Jager, W.; Apostolopoulos, V. (J. Drug Delivery, 2013)

(untitled) - Kapoor, P.; Singh, H.; Gautam, A.; Chaudhary, K.; Kumar, R.; Raghava, G. P. S. (PLoS One, 2012)

(untitled) - Carson-Jurica, M. A.; Schrader, W. T.; O'Malley, B. W. (Endocr. Rev., 1990)

(untitled) - Su, H.; Koo, J. M.; Cui, H. (J. Controlled Release, 2015)

(untitled) - Apostolopoulos, V.; Deraos, G.; Matsoukas, M.-T.; Day, S.; Stojanovska, L.; Tselios, T.; Androutsou, M.-E.; Matsoukas, J. (Bioorg. Med. Chem., 2017)

(untitled) - Lourbopoulos, A.; Deraos, G.; Matsoukas, M.-T.; Touloumi, O.; Giannakopoulou, A.; Kalbacher, H.; Grigoriadis, N.; Apostolopoulos, V.; Matsoukas, J. (Bioorg. Med. Chem., 2017)

(untitled) - Hou, J.; Diao, Y.; Li, W.; Yang, Z.; Zhang, L.; Chen, Z.; Wu, Y. (Int. J. Pharm., 2016)

(untitled) - Fung, S.; Hruby, V. J. (Curr. Opin. Chem. Biol., 2005)

(untitled) - Johnson, M.; Liu, M.; Struble, E.; Hettiarachchi, K. (J. Pharm. Biomed. Anal., 2015)

(untitled) - Pierschbacher, M. D.; Ruoslahti, E. (Nature, 1984)

(untitled) - Kapp, T. G.; Rechenmacher, F.; Neubauer, S.; Maltsev, O. V.; Cavalcanti-Adam, E. A.; Zarka, R.; Reuning, U.; Notni, J.; Wester, H.-J.; Mas-Moruno, C.; Spatz, J.; Geiger, B.; et al. (Sci. Rep., 2017)

(untitled) - Schwartz, M. A.; Schaller, M. D.; Ginsberg, M. H. (Annu. Rev. Cell Dev. Biol., 1995)

(untitled) - Plow, E. F.; Haas, T. A.; Zhang, L.; Loftus, J.; Smith, J. W. (J. Biol. Chem., 2000)

(untitled) - Gilad, Y.; Firer, M.; Gellerman, G. (Biomedicines, 2016)

(untitled) - Cox, D.; Brennan, M.; Moran, N. (Nat. Rev. Drug Discovery, 2010)

(untitled) - Chen, K.; Chen, X. (Theranostics, 2011)

(untitled) - Kumar, C. C. (Curr. Drug Targets, 2003)

(untitled) - Ganguly, K. K.; Pal, S.; Moulik, S.; Chatterjee, A. (Cell Adhes. Migr., 2013)

(untitled) - Liu, Z.; Wang, F.; Chen, X. (Drug Dev. Res., 2008)

(untitled) - Cai, W.; Chen, X. (Anti-Cancer Agents Med. Chem., 2006)

(untitled) - Burkhart, D. J.; Kalet, B. T.; Coleman, M. P.; Post, G. C.; Koch, T. H. (Mol. Cancer Ther., 2004)

(untitled) - Gilad, Y.; Noy, E.; Senderowitz, H.; Albeck, A.; Firer, M. A.; Gellerman, G. (Pept. Sci., 2016)

(untitled) - Baba, Y.; Matsuo, H.; Schally, A. V. (Biochem. Biophys. Res. Commun., 1971)

(untitled) - Marelli, M. M.; Moretti, R. M.; Januszkiewicz-Caulier, J.; Motta, M.; Limonta, P. (Curr. Cancer Drug Targets, 2006)

(untitled) - Limonta, P.; Marelli, M. M.; Mai, S.; Motta, M.; Martini, L.; Moretti, R. M. (Endocr. Rev., 2012)

(untitled) - Chen, A.; Kaganovsky, E.; Rahimipour, S.; Ben-Aroya, N.; Okon, E.; Koch, Y. (Cancer Res., 2002)

(untitled) - Cheung, L. W. T.; Yung, S.; Chan, T.-M.; Leung, P. C. K.; Wong, A. S. T. (Mol. Ther., 2013)

(untitled) - Padula, A. M. (Anim. Reprod. Sci., 2005)

(untitled) - Zhu, S.; Wang, Q.; Jiang, J.; Luo, Y.; Sun, Z. (Sci. Rep., 2016)

(untitled) - Dharap, S. S.; Wang, Y.; Chandna, P.; Khandare, J. J.; Qiu, B.; Gunaseelan, S.; Sinko, P. J.; Stein, S.; Farmanfarmaian, A.; Minko, T. (Proc. Natl. Acad. Sci. U. S. A., 2005)

(untitled) - Schally, A. V.; Nagy, A. (Eur. J. Endocrinol., 1999)

(untitled) - Laimou, D.; Katsila, T.; Matsoukas, J.; Schally, A.; Gkountelias, K.; Liapakis, G.; Tamvakopoulos, C.; Tselios, T. (Eur. J. Med. Chem., 2012)

(untitled) - Katsila, T.; Balafas, E.; Liapakis, G.; Limonta, P.; Marelli, M. M.; Gkountelias, K.; Tselios, T.; Kostomitsopoulos, N.; Matsoukas, J.; Tamvakopoulos, C. (J. Pharmacol. Exp. Ther., 2011)

Handbook of Biologically Active Peptides - Martinez, V. (Chapter 180 - Somatostatin A2, 2013)

(untitled) - Keskin, O.; Yalcin, S. (OncoTargets Ther., 2013)

(untitled) - Lahlou, H.; Guillermet, J.; Hortala, M.; Vernejoul, F.; Pyronnet, S.; Bousquet, C.; Susini, C. (Ann. N. Y. Acad. Sci., 2004)

(untitled) - Sun, L.-C.; Coy, D. H. (Curr. Drug Delivery, 2011)

(untitled) - Modlin, I. M.; Pavel, M.; Kidd, M.; Gustafsson, B. I. (Aliment. Pharmacol. Ther., 2010)

(untitled) - Lelle, M.; Kaloyanova, S.; Freidel, C.; Theodoropoulou, M.; Musheev, M.; Niehrs, C.; Stalla, G.; Peneva, K. (Mol. Pharmaceutics, 2015)

(untitled) - Sun, L.-C.; Mackey, L. V.; Luo, J.; Fuselier, J. A.; Coy, D. H. (Clin. Med.: Oncol., 2008)

(untitled) - Fuselier, J. A.; Sun, L.; Woltering, S. N.; Murphy, W. A.; Vasilevich, N.; Coy, D. H. (Bioorg. Med. Chem. Lett., 2003)

(untitled) - Grandal, M. V.; Madshus, I. H. (J. Cell. Mol. Med., 2008)

(untitled) - Li, Z.; Zhao, R.; Wu, X.; Sun, Y.; Yao, M.; Li, J.; Xu, Y.; Gu, J. (FASEB J., 2005)

(untitled) - Ai, S.; Jia, T.; Ai, W.; Duan, J.; Liu, Y.; Chen, J.; Liu, X.; Yang, F.; Tian, Y.; Huang, Z. (Br. J. Pharmacol., 2013)

(untitled) - Orbán, E.; Manea, M.; Marquadt, A.; Bánóczi, Z.; Csık, G.; Fellinger, E.; Bősze, S.; Hudecz, F. (Bioconjugate Chem., 2011)

(untitled) - Wang, X.-F.; Birringer, M.; Dong, L. F.; Veprek, P.; Low, P.; Swettenham, E.; Stantic, M.; Yuan, L.-H.; Zobalova, R.; Wu, K.; Ledvina, M.; Ralph, S. J.; et al. (Cancer Res., 2007)

(untitled) - Bertrand, Y.; Currie, J.-C.; Demeule, M.; Régina, A.; Ché, C.; Abulrob, A.; Fatehi, D.; Sartelet, H.; Gabathuler, R.; Castaigne, J.-P.; Stanimirovic, D.; Béliveau, R. (J. Cell. Mol. Med., 2010)

(untitled) - Li, Y.; Zheng, X.; Gong, M.; Zhang, J. (Oncotarget, 2016)

(untitled) - Li, F.; Tang, S.-C. (Genes Dis., 2017)

(untitled) - Teesalu, T.; Sugahara, K. N.; Ruoslahti, E. (Front. Oncol., 2013)

(untitled) - Sugahara, K. N.; Teesalu, T.; Karmali, P. P.; Kotamraju, V. R.; Agemy, L.; Girard, O. M.; Hanahan, D.; Mattrey, R. F.; Ruoslahti, E. (Cancer Cell, 2009)

(untitled) - Aubel-Sadron, G.; Londos-Gagliardi, D. (Biochimie, 1984)

(untitled) - Plunkett, W.; Huang, P.; Xu, Y. Z.; Heinemann, V.; Grunewald, R.; Gandhi, V. (Semin. Oncol., 1995)

(untitled) - Liu, L. F.; Desai, S. D.; Li, T.-K.; Mao, Y.; Sun, M.; Sim, S.-P. (Ann. N. Y. Acad. Sci., 2000)

(untitled) - Barbuti, A.; Chen, Z.-S. (Cancers, 2015)

(untitled) - Li, H.; Aneja, R.; Chaiken, I. (Molecules, 2013)

(untitled) - Füreder, L. M.; Berghoff, A. S.; Gatterbauer, B.; Dieckmann, K.; Widhalm, G.; Hainfellner, J. A.; Birner, P.; Bartsch, R.; Zielinski, C. C.; Preusser, M. (Neuro-Oncology, 2016)

(untitled) - Chitkara, D.; Mittal, A.; Behrman, S. W.; Kumar, N.; Mahato, R. I. (Bioconjugate Chem., 2013)

(untitled) - Garcia-Manteiga, J.; Molina-Arcas, M.; Casado, F. J.; Mazo, A.; Pastor-Anglada, M. (Clin. Cancer Res., 2003)

(untitled) - Santini, D.; Schiavon, G.; Vincenzi, B.; Cass, C. E.; Vasile, E.; Manazza, A. D.; Catalano, V.; Baldi, G. G.; Lai, R.; Rizzo, S.; Giacobino, A.; Chiusa, L.; et al. (Curr. Cancer Drug Targets, 2011)

(untitled) - Huang, P.; Chubb, S.; Hertel, L. W.; Grindey, G. B.; Plunkett, W. (Cancer Res., 1991)

(untitled) - Vargas, J. R.; Stanzl, E. G.; Teng, N. N. H.; Wender, P. A. (Mol. Pharmaceutics, 2014)

(untitled) - Xiao, H.; Verdier-Pinard, P.; Fernandez-Fuentes, N.; Burd, B.; Angeletti, R.; Fiser, A.; Horwitz, S. B.; Orr, G. A. (Proc. Natl. Acad. Sci. U. S. A., 2006)

(untitled) - Burkhart, C. A.; Berman, J. W.; Swindell, C. S.; Horwitz, S. B. (Cancer Res., 1994)

(untitled) - Murphy, T.; Yee, K. W. L. (Expert Opin. Pharmacother., 2017)

(untitled) - Wall, M. E.; Wani, M. C. (J. Ethnopharmacol., 1996)

(untitled) - Wall, M. E.; Wani, M. C.; Cook, C. E.; Palmer, K. H.; McPhail, A. T.; Sim, G. A. (J. Am. Chem. Soc., 1966)

(untitled) - Znojek, P.; Willmore, E.; Curtin, N. J. (Br. J. Cancer, 2014)

(untitled) - Dharap, S. S.; Qiu, B.; Williams, G. C.; Sinko, P.; Stein, S.; Minko, T. (J. Controlled Release, 2003)

(untitled) - Sun, L.; Fuselier, J. A.; Coy, D. H. (Drug Delivery, 2004)

(untitled) - Lee, M. H.; Kim, J. Y.; Han, J. H.; Bhuniya, S.; Sessler, J. L.; Kang, C.; Kim, J. S. (J. Am. Chem. Soc., 2012)

(untitled) - Gondi, C. S.; Rao, J. S. (Expert Opin. Ther. Targets, 2013)

(untitled) - Chang, M.; Zhang, F.; Wei, T.; Zuo, T.; Guan, Y.; Lin, G.; Shao, W. (J. Drug Targeting, 2016)

(untitled) - Szlachcic, A.; Zakrzewska, M.; Lobocki, M.; Jakimowicz, P.; Otlewski, J. (Drug Des., Dev. Ther., 2016)

(untitled) - Naqvi, S. A. R.; Matzow, T.; Finucane, C.; Nagra, S. A.; Ishfaq, M. M.; Mather, S. J.; Sosabowski, J. (Cancer Biother. Radiopharm., 2010)

(untitled) - Zhu, L.; Wang, T.; Perche, F.; Taigind, A.; Torchilin, V. P. (Proc. Natl. Acad. Sci. U. S. A., 2013)

(untitled) - van Duijnhoven, S. M. J.; Robillard, M. S.; Nicolay, K.; Grüll, H. (J. Nucl. Med., 2011)

(untitled) - Zhang, X.; Wang, X.; Zhong, W.; Ren, X.; Sha, X.; Fang, X. (Int. J. Nanomed., 2016)

(untitled) - Zhang, X.; Li, X.; You, Q.; Zhang, X. (Eur. J. Med. Chem., 2017)

Advances in Protein Chemistry and Structural Biology, - Vhora, I.; Patil, S.; Bhatt, P.; Misra, A. (Chapter One - Protein– and Peptide–Drug Conjugates: An Emerging Drug Delivery Technology, 2015)

(untitled) - Szabó, I.; Manea, M.; Orbán, E.; Csámpai, A.; Bősze, S.; Szabó, R.; Tejeda, M.; Gaál, D.; Kapuvári, B.; Przybylski, M.; Hudecz, F.; Mező, G. (Bioconjugate Chem., 2009)

(untitled) - Engel, J. B.; Tinneberg, H.-R.; Rick, F. G.; Berkes, E.; Schally, A. V. (Curr. Drug Targets, 2016)

(untitled) - Gaafar, R. M.; Favaretto, A. G.; Gregorc, V.; Grossi, F.; Jassem, J.; Polychronis, A.; Bidoli, P.; Tiseo, M.; O'Brien, M. E. R.; Shah, R.; Taylor, P.; Novello, S.; et al. (J. Clin. Oncol., 2015)

(untitled) - Langer, C. J.; O'Byrne, K. J.; Socinski, M. A.; Mikhailov, S. M.; Leśniewski-Kmak, K.; Smakal, M.; Ciuleanu, T. E.; Orlov, S. V.; Dediu, M.; Heigener, D.; Eisenfeld, A. J.; Sandalic, L.; et al. (J. Thorac. Oncol., 2008)

(untitled) - Curtis, K. K.; Sarantopoulos, J.; Northfelt, D. W.; Weiss, G. J.; Barnhart, K. M.; Whisnant, J. K.; Leuschner, C.; Alila, H.; Borad, M. J.; Ramanathan, R. K. (Cancer Chemother. Pharmacol., 2014)

(untitled) - Graybill, W. S.; Coleman, R. L. (Future Oncol., 2014)

(untitled) - Mahalingam, D.; Wilding, G.; Denmeade, S.; Sarantopoulas, J.; Cosgrove, D.; Cetnar, J.; Azad, N.; Bruce, J.; Kurman, M.; Allgood, V. E.; Carducci, M. (Br. J. Cancer, 2016)

(untitled) - Bakker, W. H.; Albert, R.; Bruns, C.; Breeman, W. A. P.; Hofland, L. J.; Marbach, P.; Pless, J.; Pralet, D.; Stolz, B.; Koper, J. W.; Lamberts, S. W. J.; Visser, T. J.; et al. (Life Sci., 1991)

(untitled) - Oshima, N.; Akizawa, H.; Kitaura, H.; Kawashima, H.; Zhao, S.; Zhao, Y.; Nishijima, K.-i.; Kitamura, Y.; Arano, Y.; Kuge, Y.; Ohkura, K. (Nucl. Med. Biol., 2017)

(untitled) - Nagy, A.; Schally, A. V.; Armatis, P.; Szepeshazi, K.; Halmos, G.; Kovacs, M.; Zarandi, M.; Groot, K.; Miyazaki, M.; Jungwirth, A.; Horvath, J. (Proc. Natl. Acad. Sci. U. S. A., 1996)

(untitled) - Nagy, A.; Plonowski, A.; Schally, A. V. (Proc. Natl. Acad. Sci. U. S. A., 2000)

(untitled) - Miyazaki, M.; Nagy, A.; Schally, A. V.; Lamharzi, N.; Halmos, G.; Szepeshazi, K.; Groot, K.; Armatis, P. (J. Natl. Cancer Inst., 1997)

(untitled) - Arencibia, J. M.; Bajo, A. M.; Schally, A. V.; Krupa, M.; Chatzistamou, I.; Nagy, A. (Anti-Cancer Drugs, 2002)

(untitled) - Szepeshazi, K.; Schally, A. V.; Nagy, A.; Halmos, G.; Groot, K. (Anti-Cancer Drugs, 1997)

(untitled) - Halmos, G.; Nagy, A.; Lamharzi, N.; Schally, A. V. (Cancer Lett., 1999)

(untitled) - Letsch, M.; Schally, A. V.; Szepeshazi, K.; Halmos, G.; Nagy, A. (Clin. Cancer Res., 2003)

(untitled) - Plonowski, A.; Schally, A. V.; Nagy, A.; Groot, K.; Krupa, M.; Navone, N. M.; Logothetis, C. (Cancer Lett., 2002)

(untitled) - Gründker, C.; Völker, P.; Griesinger, F.; Ramaswamy, A.; Nagy, A.; Schally, A. V.; Emons, G. (Am. J. Obstet. Gynecol., 2002)

(untitled) - Liu, S. V.; Tsao-Wei, D. D.; Xiong, S.; Groshen, S.; Dorff, T. B.; Quinn, D. I.; Tai, Y.-C.; Engel, J.; Hawes, D.; Schally, A. V.; Pinski, J. K. (Clin. Cancer Res., 2014)

(untitled) - Yu, S. S.; Athreya, K.; Liu, S. V.; Schally, A. V.; Tsao-Wei, D.; Groshen, S.; Quinn, D. I.; Dorff, T. B.; Xiong, S.; Engel, J.; Pinski, J. (Clin. Genitourin. Cancer, 2017)

(untitled) - Emons, G.; Gorchev, G.; Harter, P.; Wimberger, P.; Stähle, A.; Hanker, L.; Hilpert, F.; Beckmann, M. W.; Dall, P.; Gründker, C.; Sindermann, H.; Sehouli, J. (Int. J. Gynecol. Cancer, 2014)

(untitled) - Engel, J.; Emons, G.; Pinski, J.; Schally, A. V. (Expert Opin. Invest. Drugs, 2012)

(untitled) - Cai, R. Z.; Szoke, B.; Lu, R.; Fu, D.; Redding, T. W.; Schally, A. V. (Proc. Natl. Acad. Sci. U. S. A., 1986)

(untitled) - Schally, A. V.; Nagy, A. (Trends Endocrinol. Metab., 2004)

(untitled) - Engel, J. B.; Schally, A. V.; Halmos, G.; Baker, B.; Nagy, A.; Keller, G. (Cancer, 2005)

(untitled) - Régina, A.; Demeule, M.; Ché, C.; Lavallée, I.; Poirier, J.; Gabathuler, R.; Béliveau, R.; Castaigne, J.-P. (Br. J. Pharmacol., 2008)

(untitled) - Pardridge, W. M. (NeuroRx, 2005)

(untitled) - Banks, W. A. (BMC Neurol., 2009)

(untitled) - Etame, A. B.; Diaz, R. J.; Smith, C. A.; Mainprize, T. G.; Hynynen, K.; Rutka, J. T. (Neurosurg. Focus, 2012)

(untitled) - Thanou, M.; Gedroyc, W. (J. Drug Delivery, 2013)

(untitled) - Drappatz, J.; Brenner, A.; Wong, E. T.; Eichler, A.; Schiff, D.; Groves, M. D.; Mikkelsen, T.; Rosenfeld, S.; Sarantopoulos, J.; Meyers, C. A.; Fielding, R. M.; Elian, K.; et al. (Clin. Cancer Res., 2013)

(untitled) - Ché, C.; Yang, G.; Thiot, C.; Lacoste, M.-C.; Currie, J.-C.; Demeule, M.; Régina, A.; Béliveau, R.; Castaigne, J.-P. (J. Med. Chem., 2010)

(untitled) - Manea, M.; Mezo, G. (Protein Pept. Lett., 2013)

(untitled) - Orbán, E.; Mező, G.; Schlage, P.; Csík, G.; Kulić, Ž.; Ansorge, P.; Fellinger, E.; Möller, H. M.; Manea, M. (Amino Acids, 2011)

(untitled) - Schlage, P.; Mező, G.; Orbán, E.; Bősze, S.; Manea, M. (J. Controlled Release, 2011)

(untitled) - Murányi, J.; Gyulavári, P.; Varga, A.; Bökönyi, G.; Tanai, H.; Vántus, T.; Pap, D.; Ludányi, K.; Mező, G.; Kéri, G. (J. Pept. Sci., 2016)

(untitled) - Mezö, I.; Lovas, S.; Pályi, I.; Vincze, B.; Kálnay, A.; Turi, G.; Vadász, Z.; Seprödi, J.; Idei, M.; Tóth, G.; Gulyás, É.; Ötvös, F.; et al. (J. Med. Chem., 1997)

Amino Acids, Peptides and Proteins - Mezo, G. (Peptide and protein based pharmaceuticals)

(untitled) - Manea, M.; Leurs, U.; Orbán, E.; Baranyai, Z.; Öhlschläger, P.; Marquardt, Á.; Schulcz, A.; Tejeda, M.; Kapuvári, B.; Tóvári, J.; Mező, G. (Bioconjugate Chem., 2011)

(untitled) - Hegedüs, R.; Manea, M.; Orbán, E.; Szabó, I.; Kiss, É.; Sipos, É.; Halmos, G.; Mező, G. (Eur. J. Med. Chem., 2012)

(untitled) - Kapuvári, B.; Hegedüs, R.; Schulcz, Á.; Manea, M.; Tóvári, J.; Gacs, A.; Vincze, B.; Mező, G. (Invest. New Drugs, 2016)

(untitled) - Leurs, U.; Mező, G.; Orbán, E.; Öhlschläger, P.; Marquardt, A.; Manea, M. (Pept. Sci., 2012)

(untitled) - Leurs, U.; Lajkó, E.; Mező, G.; Orbán, E.; Öhlschläger, P.; Marquardt, A.; Kőhidai, L.; Manea, M. (Eur. J. Med. Chem., 2012)

(untitled) - Hegedüs, R.; Pauschert, A.; Orbán, E.; Szabó, I.; Andreu, D.; Marquardt, A.; Mező, G.; Manea, M. (Pept. Sci., 2015)

(untitled) - Chintalgattu, V.; Rees, M. L.; Culver, J. C.; Goel, A.; Jiffar, T.; Zhang, J.; Dunner, K., Jr; Pati, S.; Bankson, J. A.; Pasqualini, R.; Arap, W.; Bryan, N. S.; et al. (Sci. Transl. Med., 2013)

(untitled) - Vrettos, E. I.; Sayyad, N.; Mavrogiannaki, E. M.; Stylos, E.; Kostagianni, A. D.; Papas, S.; Mavromoustakos, T.; Theodorou, V.; Tzakos, A. G. (RSC Adv., 2017)

(untitled) - Ishiguro, S.; Kawabata, A.; Zulbaran-Rojas, A.; Monson, K.; Uppalapati, D.; Ohta, N.; Inui, M.; Pappas, C. G.; Tzakos, A. G.; Tamura, M. (Biochem. Biophys. Res. Commun., 2018)